Pronunciation and Spelling Accuracy in English Words with Initial and Final Consonant Clusters by Arabic-Speaking EFL Learners - Abdel Rahman Mitib Altakhaineh; Najwa Ahmad AL-Junaid; Afakh Said Younes (Languages, 2024)
Arabic phonotactics significantly differ from English phonotactics in that they usually follow a framework that forbids the presence of consonant clusters in syllabic onsets. This study examines the relationship between Arabic-speaking EFL learners’ spelling accuracy and pronunciation, concentrating on the difficulties caused by consonant clusters in initial and final positions. A mixed-methods approach was employed, involving audio recordings to assess pronunciation accuracy and a spelling test to evaluate spelling performance. According to the results, words with initial consonant clusters (clusters at the beginning of a syllable, or onset) are harder to pronounce and spell than words with final consonant clusters (clusters that follow the vowel). Initial consonant clusters are considered to demand a quick transition in consonants at the start of a syllable, requiring more exact articulation. On the other hand, final clusters allow for a more progressive and straightforward articulation by involving a consonant transition following the initial vowel sound. Additionally, epenthesis may be used as a method to break up consonant clusters in L1 phonological interference, which is consistent with Arabic phonotactic patterns.